2017
DOI: 10.1111/desc.12534
|View full text |Cite
|
Sign up to set email alerts
|

From prioritizing objects to prioritizing cues: a developmental shift for cognitive control

Abstract: Emerging cognitive control supports increasingly adaptive behaviors and predicts life success, while low cognitive control is a major risk factor during childhood. It is therefore essential to understand how it develops. The present study provides evidence for an age-related shift in the type of information that children prioritize in their environment, from objects that can be directly acted upon to cues signaling how to act. Specifically, gaze patterns recorded while 3- to 12-year-olds and adults engaged in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 39 publications
6
29
0
Order By: Relevance
“…This study created a version of the AX‐CPT for very young children that could be used with acquisition of EEG. Data from this study were consistent with other studies suggesting older children (e.g., 9‐year‐olds) observe and use environmental cues to in order to complete a goal, whereas younger children (e.g., 5‐year‐olds) use instantaneous stimulus‐related information to drive their responding (Chatham et al, 2009; Chevalier, Dauvier, & Blaye, 2018; Chevalier et al, 2014; Lorsbach & Reimer, 2010; Lucenet & Blaye, 2014). The consistency of findings was an important validation of the new task, given that slight alterations in task timings and trial proportions were necessary for the calculation of ERPs.…”
Section: Discussionsupporting
confidence: 89%
“…This study created a version of the AX‐CPT for very young children that could be used with acquisition of EEG. Data from this study were consistent with other studies suggesting older children (e.g., 9‐year‐olds) observe and use environmental cues to in order to complete a goal, whereas younger children (e.g., 5‐year‐olds) use instantaneous stimulus‐related information to drive their responding (Chatham et al, 2009; Chevalier, Dauvier, & Blaye, 2018; Chevalier et al, 2014; Lorsbach & Reimer, 2010; Lucenet & Blaye, 2014). The consistency of findings was an important validation of the new task, given that slight alterations in task timings and trial proportions were necessary for the calculation of ERPs.…”
Section: Discussionsupporting
confidence: 89%
“…Whereas proactive control supposes keeping in mind contextual information (which includes the goal), reactive control implies retrieving this contextual information ''just in time" when presented with the stimulus requiring a response. The fact that the presence of a goal cue in our WM task did not allow kindergarteners to prepare themselves for the future recall is in line with the developmental studies concluding at kindergarteners' difficulty in engaging proactive control (Chevalier & Blaye, 2016;Chevalier, Dauvier, & Blaye, 2018). Hence, the lack of benefit induced by our goal cues can be due to kindergarteners' reactive processing.…”
Section: Discussionsupporting
confidence: 73%
“…Previous research has shown that eye-tracking is a sensitive measure of attentional differences between children with and without ASD [ 61 , 62 ]. To date, the use of eye-tracking to study attentional set-shifting has been limited to older TD children and adults [ 63 , 64 ]. Second, in this novel paradigm with low task demands, both TD children and children with ASD showed successful attentional set-shifting at 2 years of age.…”
Section: Discussionmentioning
confidence: 99%